2023
DOI: 10.3390/agronomy13020559
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Futuristic Climate Variables on Weed Biology and Herbicidal Efficacy: A Review

Abstract: Our changing climate will likely have serious implications on agriculture production through its effects on food and feed crop yield and quality, forage and livestock production, and pest dynamics, including troublesome weed control. With regards to weeds, climatic variables control many plant physiology functions that impact flowering, fruiting, and seed dormancy; therefore, an altered climate can result in a weed species composition shift within agro-ecosystems. Weed species will likely adapt to a changing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 92 publications
0
1
0
Order By: Relevance
“…The activity and selectivity of herbicides are affected by various factors, such as temperature, moisture, soil texture, weed biology, physiological, and biochemical processes [1][2][3], and thus, the amount of herbicides reaching weeds is actually a small percentage of the pesticides applied [4,5]. It is, therefore, logical to enhance the application of pesticides to deliver more potent ingredients directly to the targeted weeds, thereby enabling the application of the smallest possible dose of herbicide.…”
Section: Introductionmentioning
confidence: 99%
“…The activity and selectivity of herbicides are affected by various factors, such as temperature, moisture, soil texture, weed biology, physiological, and biochemical processes [1][2][3], and thus, the amount of herbicides reaching weeds is actually a small percentage of the pesticides applied [4,5]. It is, therefore, logical to enhance the application of pesticides to deliver more potent ingredients directly to the targeted weeds, thereby enabling the application of the smallest possible dose of herbicide.…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of CO 2 reduce stomatal conductance, which can alter the efficacy of foliar herbicides [6]. Some studies have indicated that the efficacy of glyphosate in controlling Paspalum dilatatum, Conyza canadensis, and Chenopodium album could be reduced at high CO 2 concentrations [7][8][9]. When herbicides are sprayed on weed leaves at high temperatures, leaf cuticles become more fluid and more readily penetrated by fat-soluble compounds, thus demonstrating low selectivity [10].…”
Section: Introductionmentioning
confidence: 99%
“…Climate change can affect weed biology, weed dynamics, phenology, and management by affecting various physiological and biochemical processes. Weed plants react to the changing climate, which has serious consequences for weed management, especially using herbicides [28,29].…”
Section: Introductionmentioning
confidence: 99%